อิทธิพลของการกระตุ้นเชิงกลต่อการเจริญเติบโตและการสะสมกรดซาลิไซลิกของต้นกล้าข้าวพันธุ์หอมธรรมศาสตร์ - จิตจักร, วรรณระวี; ชคตระการ, สมชาย; อธินุวัฒน์, ดุสิต (Thai Journal of Science and Technology, 2020)
The aim of this study was to determine the effect of touching frequency and duration of mechanical stimulation on the growth and salicylic accumulation of Hom Thammasat rice seedling. The experimental design was conducted in 4×3 factorial in CRD with 20 replications, including 2 factors: (1) rice seeding touching durations for 10, 20, and 30 min per time and (2) touching frequency of rice seeding for 1, 2, 3, and 4 times per day. The results revealed that Hom Thammasat rice seedling mechanical stimulated by electric duster with speed rate of 256.8 cm per min for 30 min, with 1 time per day, showed suitable plant growth index and highest significant (p ≤ 0.05) of salicylic acid accumulation in rice seedling with 3.084±0.272 to 7.219±0.399 mg per g fresh weight. Our results are alternative methods for the farmers to apply to rice seedling before transplanting in paddy field for preventing plants from stress conditions.